Assessment of Morelian Meteoroid Impact on Mexican Environment - Maria A. Sergeeva; Vladislav V. Demyanov; Olga A. Maltseva; Artem Mokhnatkin; Mario Rodriguez-Martinez; Raul Gutierrez; Artem M. Vesnin; Victor Jose Gatica-Acevedo; Juan Americo Gonzalez-Esparza; Mark E. Fedorov; Tatiana V. Ishina; Marni Pazos; et al. (Atmosphere, 2021)
Possible ionospheric effects of the Morelian meteoroid that passed and exploded over Mexico on 19 February 2020 (18 February 2020 local time) were estimated. The meteoroid trajectory, velocity and time of occurrence were calculated based on outdoor camera records. Modeling was used to estimate the meteoroid initial diameter, density, mass, velocity, energy and their change during its flight in the atmosphere. The ensemble of ionospheric scintillation indices calculated from the high-rate GNSS data and the filtered slant Total Electron Content data were used to reveal the presence of ionospheric disturbances generated by shock waves excited by the meteoroid flight and explosion. The first ionospheric responses to phenomena accompanying the meteoroid were detected (2.5–3.5) min after the explosion. The disturbances were attenuated quickly with distance from their source and were rarely recorded by GNSS receivers located more than 600 km from the meteoroid explosion site. The ionospheric disturbances of intermediate-scale, small-scale, shock-acoustic-wave-scale and sometimes medium-scale were revealed. The detected disturbances corresponded to the range of acoustic-gravity waves. An asymmetry of the disturbance manifestation in different directions was observed. The obtained results are in accordance with results of the observation of other meteoroids. Although the object was smaller and of less energy than other known meteoroids, it is an interesting case because, to the best of our knowledge, it isthe first known to us low-latitude meteoroid with the detected ionospheric effects.